2014
DOI: 10.21608/ajfm.2014.18765
|View full text |Cite
|
Sign up to set email alerts
|

Medico-legal Aspects of Burned Cases Admitted to Burn Unit in Tanta University Hospital

Abstract: Background: Burns continue to be a medical, psychological and economic problem in developed and developing countries. Burns in Egypt represent a major problem as compared with heart diseases, malignancy and road accidents. Objectives: Accordingly, this work was conducted to study the medico legal aspects of burned cases and the magnitude of burn problem in Burn Unit in Tanta University Hospital. Study design: This study was cross sectional, conducted over six months where (160) burned cases admitted to Burn Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…This can be explained by unawareness of children and their exploring nature and activity in addition to lack of proper supervision from parents especially in crowded houses of low socioeconomic classes (Attia et al, 1997). This was in accordance with Heshmat et al (2014) on their study on burnt patients in burn unit in Tanta university hospital also, the same finding was found by Hassen et al (2010) in their study on burnt patients in Assiut university hospital burn unit. However, Afify et al (2012) founded that adult group of age are more affected with burn injury being the age of activity and power with increased risk to exposure to fire followed by children group.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This can be explained by unawareness of children and their exploring nature and activity in addition to lack of proper supervision from parents especially in crowded houses of low socioeconomic classes (Attia et al, 1997). This was in accordance with Heshmat et al (2014) on their study on burnt patients in burn unit in Tanta university hospital also, the same finding was found by Hassen et al (2010) in their study on burnt patients in Assiut university hospital burn unit. However, Afify et al (2012) founded that adult group of age are more affected with burn injury being the age of activity and power with increased risk to exposure to fire followed by children group.…”
Section: Discussionsupporting
confidence: 92%
“…This may be due to the high incidence of scald injuries in the current study which usually causes superficial type of injuries. The same finding was observed by Heshmat et al (2014) who found that second degree Study of Medicolegal Aspects of Burnt Cases burns were the commonest type of burn in their study in burn unit in Tanta university hospital. Jaiswal et al (2007) reported that third degree burns were the commonest type of burn in their study in India.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations